Constraints for the photolysis rate and the equilibrium constant of ClO‐dimer from airborne and balloon‐borne measurements of chlorine compounds. Issue 11 (10th June 2014) - Kleinböhl, Armin; Khosravi, Maryam; Urban, Joachim; Canty, Timothy; Salawitch, Ross J.; Toon, Geoffrey C.; Küllmann, Harry; Notholt, Justus
Abstract We analyze measurements of ClO across the terminator taken by the Airborne Submillimeter Radiometer (ASUR) in the activated vortices of the Arctic winters of 1995/1996, 1996/1997, and 1999/2000 to evaluate the plausibility of various determinations of the ClO‐dimer photolysis cross section and the rate constant controlling the thermal equilibrium between ClO‐dimer and ClO. We use measured ClO during sunlit conditions to estimate total active chlorine (ClOx). As the measurements suggest nearly full chlorine activation in winter 1999/2000, we compare ClOx estimates based on various photolysis frequencies of ClO‐dimer with total available inorganic chlorine (Cly), estimated from an N2O‐Cly correlation established by a balloon‐borne MkIV interferometer measurement. Only ClO‐dimer cross sections leading to the fastest photolysis frequencies in the literature (including the latest evaluation by the Jet Propulsion Laboratory) give ClOx mixing ratios that overlap with the estimated range of available Cly. Slower photolysis rates lead to ClOx values that are higher than available Cly. We use the ClOx calculated from sunlit ClO measurements to estimate ClO in darkness based on different equilibrium constants, and compare it with ASUR ClO measurements before sunrise at high solar zenith angles. Calculations with equilibrium constants published in recent evaluations of the Jet Propulsion Laboratory give good agreement with observed ClO mixing ratios. Equilibrium constants leading to a higher ClO/ClOx ratio in darkness yield ClO values that tend to exceed observed abundances. Perturbing the rates for the ClO + BrO reaction in a manner that increases OClO formation and decreases BrCl formation leads to lower ClO values calculated for twilight conditions after sunset, resulting in better agreement with ASUR measurements.